Fusion PCR generated Japanese encephalitis virus/dengue 4 virus chimera exhibits lack of neuroinvasiveness, attenuated neurovirulence, and a dual-flavi immune response in mice - Mathenge, E.G.M.; Parquet, M.D.C.; Funakoshi, Y.; Houhara, S.; Wong, P.F.; Ichinose, A.; Hasebe, F.; Inoue, S.; Morita, K. (Society for General Microbiology, 2004)
The first flavivirus chimera encoding dengue 4 virus (D4) PrM and E structural proteins in a Japanese encephalitis virus (JEV) backbone was successfully generated using the long-PCR based cDNA-fragment stitching (LPCRcFS) technique, demonstrating the technique's applicability for rapid preparation of flavivirus chimeras. The JEV/D4 chimera multiplied at levels equal to JEV and D4 in the mosquito cell line C6/36, while in a mouse neuronal cell line (N2a) JEV replicated efficiently, but JEV/D4 and D4 did not. In mouse challenge experiments, JEV/D4 showed a lack of neuroinvasiveness similar to D4 when inoculated intraperitoneally, but demonstrated attenuated neurovirulence (LD50=3·17×104 f.f.u.) when inoculated intracranially. It was also noted that mice receiving intraperitoneal challenge with JEV/D4 possessed D4-specific neutralization antibody and in addition clearly showed resistance to JEV intraperitoneal challenge (at 100×LD50). This suggests that immunity to anti-JEV non-structural protein(s) offers protection against JEV infection in vivo. Dengue secondary infection was also simulated by challenging mice pre-immunized with dengue 2 virus, with D4 or JEV/D4. Mice showed higher secondary antibody response to challenge with JEV/D4 than to D4, at 210 000 and 37 000 averaged ELISA units, respectively. Taken together, aside from demonstrating the LPCRcFS technique, it could be concluded that the PrM and E proteins are the major determinant of neuroinvasiveness for JEV. It is also expected that the JEV/D4 chimera with its pathogenicity in mice and atypical immune profile, could have applications in dengue prophylactic research, in vivo efficacy assessment of dengue vaccines and development of animal research on models of dengue secondary infection.